Pemanfaatan Janggel Jagung dan Batok Kelapa Menjadi Gas Mempan Bakar untuk Mensubtitusi Elpiji Melalui Proses Gasifikasi - Suhartono Suhartono (Seminar Nasional Teknik Kimia Kejuangan, 2015)
The biomass gasification is a technology which converts any kind of biomass energy which low heat value (such as waste from agriculute and forest and organic waste) into combustible gas. Biomass is combusted im-perpectly by way of controlling the flow of air into gasifier to convert solid state into gas state, generating a combustable gas which mainly consists of H2, CO, CH4 and CnHm. A small gasifier design system with 35 cm in inside diameter and 70 cm of combustion zone was used to gasified agriculture waste of corncorb and coconut shell. About 10 kg of ±3cm corncob and coconut shell was gasified in this gasifier. The operation time of each biomass utilization was about 1.5 hour and 2.2 hour, respectivly. The combustable gas was used as a fuel by direct combustion in an ordinary modified gas stove. The water boiling time method (WTB) was used to determined thermal efficiency of this gasifier. About 2,0 minute was needed to boiled of 5 kg of water and giving thermal efficiency ±23.50% with a fire power of 14-18 kWth. The consumption of biomass and electricity cost was calculated. The price IDR 20,00-25,00 was needed for boiling 1 kg of water.